Female Political Participation in India (Journal of Advances and Scholarly Researches in Allied Education, 2024)
Female political participation in India has seen significant evolution over the decades, with various measures introduced to promote gender equality in political spheres. Since India's independence in 1947, there has been a concerted effort to enhance women's roles in governance, particularly through legislative reforms and the establishment of local self-government institutions like the Panchayati Raj. These initiatives aimed to integrate women into political decision-making processes, offering a platform for their voices and leadership. This study employs a qualitative approach, including document analysis of relevant legislative amendments and interviews with female political leaders at different levels of government, to examine the landscape of female political participation. Although progress has been made, with increased female representation in local governance, the study uncovers ongoing challenges such as societal stereotypes, limited resources, and institutional biases that continue to affect women's full political engagement. The research underscores the need for continued reforms and supportive measures to address these challenges and advance gender equality in Indian politics.